Drivers of wildfire behaviour, severity and magnitude in the Limietberg conservation area : understanding the complexity of wildfire risk - Moir, Shaun Alexander (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2014.